PENGARUH PENDEKATAN PEMBELAJARAN DAN MINAT BACA TERHADAP PEMAHAMAN PUISI - SUHERMAN, ACHMAD (JURNAL PENDIDIKAN BAHASA DAN SASTRA, 2011)
The objective of this study is to find out the effect of the teaching approach and interest in reading on the understanding of poetry content. The teaching approach use was humanistic and structural approachs, the method used was a quasi experiment of 2x2 factorial design, the sample size was 80 student grade 8 of the public junior Highschool. The result found are as the followings; (1)The ability of student to understand comprehensively of the poetry by humanistic approach is better than by the structural approach of teaching, (2)The ability of students with the reading interest the humanistic approach is better than by the structural approach on their comprehension of the poetry contens.Keywords: understanding of poetry, teaching approach, reading interest of student.